Manajemen Kelas sebagai Upaya Guru Pendidikan Kristen dalam Meningkatkan Kedisiplinan Siswa - Sinukaban, Difa Glery; Andriani, Neneng (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Classroom management can become a strategy for teachers to manage every aspect of learning, including improving student discipline. Through the application of three classroom management, namely designing, implementing, and evaluate, it is expected to be able to develop the character of students' discipline according to the indicators, namely having responsibility, obedience, and readiness in learning. In the teacher's effort to improve discipline through classroom management, the Bible becomes the basis for teacher action, so that through the help of the Holy Spirit, students are able to know God, and carry out self-transformation, including discipline. This writing aims to examine the application of classroom management as a form of teacher effort in improving the discipline of second grade elementary school students. With the descriptive research method, it is concluded that classroom management can improve student discipline, but measuring study results and learning objectives might need to be conducted for the next research.